Institute of prostitution in Japanese culture - Yarotskaya, Yuliya A. (Human in the Socio-Cultural Dimension, 2020)
The article deals with the historical and cultural aspects of the development of prostitution in the Japanese islands. The text gives a reflection of prostitution in the literary monuments. It is dealt with the history of the unification of all the houses of pleasure in a single quarter (for example, the Yoshiwara’s quarter in modern Tokyo). The text gives a description of the various classes of courtesans (tayū, kōshi, sancha) and kamuro, their personal students. In addition, the article provides a description of tea houses which was intended for the provision of sexual services by courtesans.